Effect of Planting Media Composition and NPK Dosage on The Growth and Production of Shallots (Allium Cepa L.) Thailand Varieties - Ahmad Izzan Nabil Farid; Helilusiatiningsih, Nunuk; Tri Handayani (Journal of Soilscape and Agriculture, 2022)
The purpose of this research is to analyzed the interaction between the composition of the growing media and the dose of NPK on the growth and production of shallot (Allium cepa L.).The hypothesis put forward in this study is,It is suspected that there is an interaction between the composition of the growing media and the dose of NPK on the growth and production of shallot (Allium cepa L.). The benefits that can be obtained in this study are: 1. Gaining technical experience in onion cultivation with certain treatments, 2. As a material for providing final project evaluations, 3. As a reference for the community about onion cultivation with certain treatments.This research was conducted at the UNISKA Integrated Field Laboratory Greenhouse using polybags, located in Rejomulyo Village, Kediri City District, with an altitude of 67 meters above sea level, tropical climate with an average temperature of 30ºC and has an average rainfall of 1,500–2,000 mm per year. Has a sandy loam soil type. This research was conducted using a completely randomized design (CRD) with 3×3 factorial pattern, with 9 combinations of 3 replications. Factor I is planting media, which consists of three types, and Factor II is NPK dose. From these two factors, 9 treatment combinations were obtained and repeated 3 times. There was no interaction between the composition of the growing media and the dose of NPK on the growth and production of shallots.There was a single effect, the composition of the growing media had a significant effect on the growth.